2019
DOI: 10.1002/fsn3.1296
|View full text |Cite
|
Sign up to set email alerts
|

Silkworm pupa oil attenuates acetaminophen‐induced acute liver injury by inhibiting oxidative stress‐mediated NF‐κB signaling

Abstract: Acetaminophen (APAP) overdose causes severe hepatotoxicity and acute liver failure. The current study aims to investigate the protection effects of silkworm pupa oil (SPO) against acute hepatic injury in APAP‐exposed Kunming mice. Our results showed that the liver index and the levels of serum alanine transaminase (ALT) and aspartate transaminase (AST) in mice subjected to APAP treatment were decreased by SPO. Supplement of SPO also restored hepatic histopathological alterations induced by APAP. The APAP‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Previous results showed that after an APAP overdose activation of NF-κB-mediated signaling triggers oxidative stress and a pro-inflammatory response, ultimately causing liver damage [ 21 , 30 , 31 ]. To determine whether NF-κB signaling is modulated in the liver by chronic and infratherapeutic APAP administration, nuclear p65-NF-κB and cytosolic IκBα protein levels were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results showed that after an APAP overdose activation of NF-κB-mediated signaling triggers oxidative stress and a pro-inflammatory response, ultimately causing liver damage [ 21 , 30 , 31 ]. To determine whether NF-κB signaling is modulated in the liver by chronic and infratherapeutic APAP administration, nuclear p65-NF-κB and cytosolic IκBα protein levels were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress caused by abnormal expression of these indicators is involved in the pathogenesis of many clinical diseases [29]. GSH is also an active peptide with good antioxidant effect, which can effectively regulate the oxidation balance of the body and inhibit the damage caused by oxidative stress [30]. The results of this study also showed that MDLF can interfere with the abnormality of oxidation-related indexes after H 2 O 2 treatment of cells, and thus, it reduces the cell damage caused by oxidative stress and plays a role in protecting the normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence indicates that the use of silkworm pupae oil reduces oxidative damage and inflammatory responses in mice [ 69 ]. Silkworm pupae oil also reduced acetaminophen-induced acute liver injury and alcohol-induced hepatotoxicity and oxidative stress in mice by inhibiting the oxidative-stress-mediated NF-κB signalling pathway [ 67 , 68 ]. Silkworm pupae might serve as a potential drug resource for the treatment of gastric ulcers and the prevention of acute liver injury.…”
Section: Pharmacological Functions and Mechanisms Of Silkworm Pupaementioning
confidence: 99%